Global perspectives on green business administration and sustainable supply chain management - Khan, Syed Abdul Rehman, 1987- (Business Science Reference (an imprint of IGI Global), 2020)
""This book discusses innovative green practices including recycling, remanufacturing, reduction in waste and adoption of renewable energy in manufacturing. It also examines environmentally friendly policies that have been adopted by many European and Western countries"--Provided by publisher"-- Provided by publisher.
Keywords: Management -- Environmental aspects.; Business logistics -- Environmental aspects.; elektronické knihy; electronic books